PEER SOCIAL SUPPORT, ADVERSITY QUOTIENT, AND SELF-EFFICACY ON ACADEMIC RESILIENCE AMONG VOCATIONAL SCHOOLS STUDENTS - Sariwulan, Rd. Tuty; Wahono, Puji; Amelia, Mutiara Putri (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
Academic resilience has a vital role to ensure students have high resilience in completing their academic studies. This study aims to determine the direct influence of Peer Social Support, Adversity Quotient, and Self-Efficacy on the Academic Resilience in Class X Students at SMKN 48 Jakarta. The method used is quantitative through statistical analysis on multiple linear regression with the IBM SPSS version 24.0 program. The sampling technique used proportionate stratified sampling with the Slovin formula at an error rate of 5%, namely 166 students. Then data collection was carried out based on a survey and filling out a questionnaire using a Likert scale. Data analysis techniques in this study consisted of instrument test, analysis requirements test, classical assumption test, hypothesis test, and coefficient of determination test. Through the results of regression analysis, the research equation is Y = 9,484 + (0,138X1) + (0,230X2) + (0,163X3) + 0,765 with a contribution percentage value of 41,4%. Based on data calculations, the results of this study indicate that there is a positive and significant between Peer Social Support, Adversity Quotient, and Self-Efficacy on Academic Resilience either simultaneously or partially.